NEW EVIDENCE ON THE HECKMAN CURVE. (17th December 2019) - Rea, David; Burton, Tony
Abstract: The Heckman Curve characterizes the rate of return to public investments in human capital as rapidly diminishing with age. For the disadvantaged, it describes investments early in the life course as having significantly higher rates of return compared to later in life. This paper assesses the Heckman Curve using estimates of program benefit cost ratios from the Washington State Institute for Public Policy. We find no support for the claim that social policy programs targeted early in the life course have the largest benefit cost ratios, or that on average the benefits of adult programs are less than the cost of the intervention.